Epigallocatechin gallate attenuates experimental non-alcoholic steatohepatitis induced by high fat diet - Kuzu, Nalan; Bahcecioglu, Ibrahim Halil; Dagli, Adile Ferda; Ozercan, Ibrahim Hanifi; Ustuendag, Bilal; Şahin, Kazım (Wiley, 2008)
Background and Aim: In the present study, we examined the preventive role of epigallocatechin gallate (EGCG) in an experimental non-alcoholic steatohepatitis model induced by a high fat diet. Methods: The study included 21 male Sprague-Dawley rats, which were equally divided into three groups. The first group was fed on a standard rat diet, the second group on a high fat diet (HFD), and the third group on a HFD + EGCG. The study concluded after 6 weeks. Histopathological examination was performed. Plasma and tissue MDA levels, glucose, insulin, alanine aminotransferase (ALT), aspartate aminotransferase, gamma glutamyltransferase, alkaline phosphatase, triglyceride, and cholesterol levels were studied. Insulin resistance was calculated by the homeostasis model of insulin resistance method. Results: Steatosis, inflammation, ballooning degeneration, and necrosis increased significantly in the HFD group, compared to the control group (P < 0.01). Steatosis and inflammation decreased in the HFD + EGCG group, in comparison to the HFD group (P < 0.05, for each). There was a significant decline in ALT (P < 0.01), triglyceride (P < 0.01), insulin (P < 0.05), and glucose (P < 0.05) levels in the HFD + EGCG group, when compared to the HFD group. Plasma and liver MDA levels in the HFD + EGCG group were lower than those of the HFD group; the difference was significant (P < 0.01 for each). Glutathione levels in the HFD + EGCG group was significantly higher those in the HFD group. CYP 2E1 and alpha-smooth muscle actin expression decreased in the HFD + EGCG group, in comparison to the HFD group (P < 0.01, P < 0.05, respectively). Conclusion: EGCG reduces the development of experimental non-alcoholic steatohepatitis induced by a high fat diet. It seems to exercise this effect through its effect on lipid metabolism and antioxidant characteristics.
Keywords: epigallocatechin gallate; high fat diet; non-alcoholic fatty liver; steatohepatitis